Exchange Rate Volatility and Oil Prices in South Africa - Hlongwane, Nyiko Worship; Daw, Olebogeng David; Shogole, Leeto; Ribese, Selinah (International Journal of Energy Economics and Policy, 2022)
The study examines the oil prices and exchange rate volatilities in South Africa. The study employs monthly time series data spanning for the period from 1960 M1 to 2021M11 using data collected from the SARB. The study employs a TGARCH model to analyse the volatilities between oil prices and exchange rate. The study found that oil prices have a negative statistically significant impact on the exchange rates in South Africa. The study therefore recommends that the monetary authorities must monitor oil prices as they have an ability to cause exchange rate volatilities.